Selection of mother tongue on ethnic Osing family (Sociolinguistic and ethnographic communication studies) - Memmy Dwi Jayanti (Universitas Indraprasta PGRI, 2017)
The purpose of this study to describe the language selection mom used ethnic Osing Giri in the distric, the village of Penataban, Banyuwangi-East Java. The language used is the language communities in Banyuwangi Osing, Java, and Madura for the third ethnic coexistence. Womg Osing or Lare Osing is a native of Banyuwangi, Osing language is a direct descendant of the ancient Javanese language yet very different dialect. The method used is descriptive method of providing data refer capably involved (SLC), consider ably involved free (SBLC), and interview. The results showed that the choice of language on ethnic family Osing Indonesian in there is an influence in terms of education and employment. Indonesia introduced the use of language in children is the language used in everyday family. Such circumstances indicate that the Indonesian experience growth in public life, expecially in rural districts Penataban Giri, Banyuwangi